THE PRINCIPLES OF YUGOSLAV CULTURAL POLICY (1945-1952) (Filološke pripombe, 2021)
After World War II and the formation of the new Yugoslav state, the Communist Party of Yugoslavia began to establish a new political system. In the process of transformation of Yugoslav society, the resource of culture was crucial. The paper focuses on the basic principles upon which the cultural policy in the new Yugoslavia was built, whose specificity was largely conditioned by the current political and educational situation. Based on the available archival material, the paper analyzes the fundamental ideas in the specific field, in the periods before and after the conflict with the Information Bureau (Cominform). The differences between the two periods show how important the social factors are in the formulation of the goals of the cultural policy. Namely, in the first years there is a strong sovietization in the cultural field, where the following of the Soviet models in politics is especially noticeable. In the 1950s began desovietization, а process that consisted of abandoning the Soviet model of cultural practices, abandonment of the ideological matrix of socialist realism and introduction of self-administrative socialism, which would contribute to a certain democratization in the field of cultural production.